Jobsheet AUTO CAD: Solusi Peningkatan Keaktifan dan Prestasi Mahasiswa Otomotif - suyitno (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to: (1) Increase the learning activity of automotive engineering education students at Muhammadiyah University of Purworejo. (2) Improving student learning achievement. (3) To find out how much increase in student activity and learning achievement. This research is a quantitative type of classroom action research. The research flow consists of planning - giving questionnaires - giving treatment - giving questionnaires - giving questions - giving questions. The research subject is class A for the academic year 2021/2022 with 25 students. Data collection techniques were carried out with questionnaires and questions. Based on the research that has been done, it can be concluded that the use of jobsheets can increase student activity and achievement. The learning activity of students increased which initially (before treatment) was only 70.76% increased to 72.08% (after treatment). Meanwhile, the learning achievement of students above the KKM increased from 36.11% (before treatment) to 63.22% in the first cycle and increased to 91.67% in the second cycle. The research was conducted in two cycles, because the activeness and learning achievement of students had increased beyond the indicators of success. Keywords: jobsheet, activity, achievement, automotive